Geographies Of Tolerance: Hiding the Lyme Disease Epidemic in Scotland’s Landscapes - Ritti Soncco (Engaging Science, Technology, and Society)
Little research has been conducted on the relationship between Lyme disease and the landscapes in which people became infected. This article remedies this gap by researching the interplay of environment, ticks, bacteria, and humans. Based on fieldwork across Scotland in 2018–2020, this article explores the tension of Scottish landscapes as both beautiful and as having the highest incidence of Lyme disease in Europe. I introduce the people living with chronic Lyme disease and the epidemiologists and entomologists researching Lyme disease in Scotland, and explore their relationships to the landscapes of the bacteria. Introducing the theoretical framework ‘geographies of tolerance’, I explore how Scottish landscapes are constructed as safe and healthy: an exploration of how spaces are constructed around ideas of safety, and how this safety is extended to the animals, microbes, and diseases found within those spaces. Perceived as fundamentally safe, any potential dangers encountered in spaces are thereby tolerated and the possibility of danger becomes invisible. Finally, I apply geographies of tolerance to make sense of Britain’s response to the Covid-19 pandemic and the impact that lockdown had on rendering B. burgdorferi more tolerable and more invisible.